Targeting inflammation and immune activation to improve CTLA4-Ig-based modulation of transplant rejection - Iglesias, Marcos; Brennan, Daniel C.; Larsen, Christian P.; Raimondi, Giorgio (Frontiers in Immunology, 2022)
For the last few decades, Calcineurin inhibitors (CNI)-based therapy has been the pillar of immunosuppression for prevention of organ transplant rejection. However, despite exerting effective control of acute rejection in the first year post-transplant, prolonged CNI use is associated with significant side effects and is not well suited for long term allograft survival. The implementation of Costimulation Blockade (CoB) therapies, based on the interruption of T cell costimulatory signals as strategy to control allo-responses, has proven potential for better management of transplant recipients compared to CNI-based therapies. The use of the biologic cytotoxic T-lymphocyte associated protein 4 (CTLA4)-Ig is the most successful approach to date in this arena. Following evaluation of the BENEFIT trials, Belatacept, a high-affinity version of CTLA4-Ig, has been FDA approved for use in kidney transplant recipients. Despite its benefits, the use of CTLA4-Ig as a monotherapy has proved to be insufficient to induce long-term allograft acceptance in several settings. Multiple studies have demonstrated that events that induce an acute inflammatory response with the consequent release of proinflammatory cytokines, and an abundance of allograft-reactive memory cells in the recipient, can prevent the induction of or break established immunomodulation induced with CoB regimens. This review highlights advances in our understanding of the factors and mechanisms that limit CoB regimens efficacy. We also discuss recent successes in experimentally designing complementary therapies that favor CTLA4-Ig effect, affording a better control of transplant rejection and supporting their clinical applicability.